On the Possible Interpretations of Amos 7:14 - Ridge, David B. (2018)
The ambiguity of the vocabulary and grammar of Amos 7:14 has led to the proposal of numerous conflicting interpretations. I present a comprehensive evaluation of these proposals. I argue that both grammar and context indicate Amos 7:14 is made up of three declarative clauses, two negative and one affirmative, which describe either the past or present vocation of Amos. Whether they describe the past or present relative to the situation in the narrative, these clauses combine with the account of Amos’s prophetic call to indicate that his prophetic activity is not motivated by economic or other concerns but only by his desire to be obedient to YHWH.
Keywords: Amos -- Amaziah -- prophet -- son of a prophet -- nominal clauses -- verbless clauses